Alleviate environmental concerns with biochar as a container substrate: a review - Yu, Ping; Qin, Kuan; Niu, Genhua; Gu, Mengmeng (Frontiers in Plant Science, 2023)
Peat moss has desirable properties as a container substrate, however, harvesting it from peatland for greenhouse/nursery production use has disturbed peatland ecosystem and caused numerous environmental concerns. More recently, many nations have taken actions to reduce or ban peat moss production to reach the carbon neutral goal and address the environmental concerns. Also, the overuse of fertilizers and pesticides with peat moss in greenhouse/nursery production adds extra environmental and economic issues. Thus, it is urgent to find a peat moss replacement as a container substrate for greenhouse/nursery production. Biochar, a carbon-rich material with porous structure produced by the thermo-chemical decomposition of biomass in an oxygen-limited or oxygen-depleted atmosphere, has drawn researchers’ attention for the past two decades. Using biochar to replace peat moss as a container substrate for greenhouse/nursery production could provide environmental and economic benefits. Biochar could be derived from various feedstocks that are regenerated faster than peat moss, and biochar possesses price advantages over peat moss when local feedstock is available. Certain types of biochar can provide nutrients, accelerate nutrient adsorption, and suppress certain pathogens, which end up with reduced fertilizer and pesticide usage and leaching. However, among the 36,474 publications on biochar, 1,457 focused on using biochar as a container substrate, and only 68 were used to replace peat moss as a container substrate component. This study provides a review for the environmental and economic concerns associated with peat moss and discussed using biochar as a peat moss alternative to alleviate these concerns.